2015
DOI: 10.5194/aab-58-379-2015
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of pork from a local and a commercial breed

Abstract: Abstract. This study investigated the effects of breed on the fatty acid compositions of the Longissimus thoracis et lumborum (LTL) of gilts and barrows. Although only one muscle was analyzed, the results gave a good indication of the effect that breed and sex may have on the fatty acid compositions of the meat. Breed exhibited a significant effect on the fatty acid composition of pigs, whereas the effects of sex were found to be minor. Higher contents of intramuscular fat (IMF), C16 : 1, C18 : 1 and monounsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
56
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 38 publications
15
56
3
1
Order By: Relevance
“…The analyzed ham varieties contained more unsaturated (with predominant share of C 18:1 (cis-9) acid) than saturated fatty acids, what is in accordance with the results received by Kasprzyk, Tyra and Babicz [21]. They were characterized by high concentrations of C 16:0 and C 18:1 (cis-9), as well as a moderate content of C 16:1 (cis-9), C 18:0 and C 18:2 (cis-9,12).…”
Section: Hamssupporting
confidence: 90%
See 1 more Smart Citation
“…The analyzed ham varieties contained more unsaturated (with predominant share of C 18:1 (cis-9) acid) than saturated fatty acids, what is in accordance with the results received by Kasprzyk, Tyra and Babicz [21]. They were characterized by high concentrations of C 16:0 and C 18:1 (cis-9), as well as a moderate content of C 16:1 (cis-9), C 18:0 and C 18:2 (cis-9,12).…”
Section: Hamssupporting
confidence: 90%
“…Since the current human diet is usually already rich in fats, especially saturated and n-6 polyunsaturated, and there is also a need to balance the n-6/n-3 fatty acid intake for prevention of chronic diseases, it is particularly essential to evaluate the fatty acid profile in daily eaten foods, such as meat products [17,19]. Yet, the composition of meat fat depends on various factors, such as the individual characteristics of the animal (age, sex, species, breed) and its diet [17,20,21]. Proper selection of raw materials can therefore have a positive effect on the fatty acid profile.…”
Section: Introductionmentioning
confidence: 99%
“…from 5.3 to 5.8 (Honikel, 1999). The higher pH value of meat of autochthonous pigs is in agreement with the research in Kasprzyk et al (2015) and may be associated with better water holding capacity and a darker colour of meat (Lawrie and Ledward, 2006). Most of the differences in the colour of the meat surface arise from the chemical state of the myoglobin molecules (Lawrie and Ledward, 2006).…”
Section: Effect Of the Breed On The Colour Characteristicssupporting
confidence: 83%
“…A previous report by Kasprzyk et al . () also showed that PUL pigs are characterised by better fatty acid composition, 1% higher IMF level ( P ≤ 0.01), higher content of palmitoleic (25%) and oleic (2%) acids and a lower n‐6:n‐3 ratio in the longissimus dorsi muscle in comparison to PL pigs. Therefore, differences in genotype frequency of deleterious missense variants were observed for the ATGL , PLA2G12A and ALDH3A2 genes, which were shown to play a role in biological processes determining fat deposition.…”
Section: Discussionmentioning
confidence: 87%